The Influence Of Perceptions Of Price And Production Quality On Consumer Satisfaction Of Minyakita Cooking Oil: - Daina, Wana; Fitriadi, Budhi Wahyu; Jakiyah, Ulpah (Utami Publisher, 2024)
Consumer satisfaction is a feeling of pleasure or disappointment from within a person that arises from comparing the perceived performance of the product. Consumer satisfaction will be obtained if the desired product meets consumer expectations. This research was conducted to determine the influence of perceived price and product quality on consumer satisfaction who consume Minyakita cooking oil, either partially or simultaneously, and then see how dominant the influence of the independent variable is on the dependent variable. In this study, the sample took 100 respondents who were determined based on the Lemeshow equation. The sampling technique in this research uses a purposive sampling technique by analyzing data using a multiple linear regression analysis model. Based on the research results, it shows that the variables of perceived price and product quality simultaneously have a positive and significant effect on the satisfaction of Minyakita consumers with a calculated F regression value of 45.159 and a significance value of 0.000 < 0.05. price perception (X1) has a partially positive and significant effect with a t-count value of 2,967 and a significance value of 0.004 < 0.05 then the product quality variable (X2) has a partial and positive effect with a t-count value of 6,378 and a significance value of 0.000 < 0, 05 on consumer satisfaction (Y). The independent variable that has a dominant influence in this research is the product quality variable which has a percentage level value of 29,59%.